Design and validation of a nutritional recipe for a snack made of green banana peel flour (Musa paradisiaca) - Acosta-Coello, Camila (2021)
This study aims to design and validate a nutritional recipe for a snack made of Green Banana (Musa paradisiaca) Peel Flour (GBPF) and to assess the nutritional composition and microbiological quality of the flour. Banana peel, a food industry by-product, is a nutritious, low-cost material available for all year. Banana peel flower could be used as a functional ingredient due to its high fiber content and good functional properties. In general, university students have a deficient dietary fiber intake due to altered dietary patterns; thus, this study was focused on this population. The GBPFs were obtained from the peels of pre-climacteric bananas by fluidized bed (FDB) dryer, after which, microbiological, proximate, and dietary fiber analyses were applied. It was designed the nutritional recipe for the snack taking into account the energy and dietary fiber nutritional requirements of the target population. It could be validated and adjusted the recipe following the methodology of Centro Nacional de Alimentaci n y Nutrici n, concluding with the determination of dietary fiber in the end-product. The dietary fiber, total carbohydrate, protein, total fat and energy contents of the GBPF were as following: 38.7 g, 76.3 g, 5.9 g, 3.6 g, and 361.2 kcal, per 100 g of flour. The snack contained 7.74 g of dietary fiber per serving size, having a good acceptance among the university students' panelists based on an organoleptic test. In conclusion, the GBPF showed great potential as a source of dietary fiber, and it was an excellent source of carbohydrates and other nutrients to a lesser degree. When included as a functional ingredient in the nutritional formulation of a snack, it had an overall positive effect on the product's organoleptic characteristics.